The application and validity of various reaction kinetic models on woody biomass pyrolysis. (15th July 2019) - Ding, Yanming; Zhang, Juan; He, Qize; Huang, Biqing; Mao, Shaohua
Abstract: The pyrolysis of woody biomass has received extensive attention due to its importance in the thermal chemical conversion and energy utilization. Due to the complexity of actual reaction scheme, the pyrolysis of wood is generally modeled on the basis of apparent kinetic models. In this paper, six classic lumped kinetic models (Models I-VI) were applied and compared with each other to analyze their sensitivity coupled with Shuffled Complex Evolution method based on the measured thermogravimetric data. The optimized kinetic parameters were used to predict the pyrolysis process, and then verify the validity of different reaction kinetic models. The results show that the existence of second tar reaction for one-component mechanism and the refinement of reactant components for multi-component mechanism can be helpful to improve the reasonability of reaction models. Eventually, the simplest global reaction Model I and second tar reaction involved one-component Models III, IV, as well as three-component parallel reaction Model V can achieve the better compatibility of reaction kinetic models and Shuffled Complex Evolution optimization, with the acceptable efficiency to describe the pyrolysis of woody biomass. Highlights: Sensitivity of commonly used TG pyrolysis kinetic models is compared. Shuffled Complex Evolution method is coupled with all reaction models. Various sets of optimized reaction kinetic parameters are obtained. Second tar reaction and reactant component refinement can improve pyrolysis model.